Introduction to solid state physics - Kittel, Charles (Singapore: John Wiley & Sons, 1996)
New edition of the most widely-used textbook on solid state physics in the world. Describes how the excitations and imperfections of actual solids can be understood with simple models that have firmly established scope and power. The foundation of this book is based on experiment, application and theory. Several significant advances in the field have been added including high temperature superconductors, quasicrystals, nanostructures, superlattices, Bloch/Wannier levels, Zener tunneling, light-emitting diodes and new magnetic materials.
Includes bibliographical references; Appendix A-J, 631-665p.; Index 667-673p.
Keywords: Solid state; State of matter; Physics